1986
DOI: 10.1148/radiology.161.2.3763907
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor of the craniovertebral junction associated with chronic subluxation: MR imaging studies.

Abstract: Masses at the craniovertebral junction generally have serious prognostic implications. However, the authors studied three patients who had chronic atlantoaxial subluxation from either degenerative disease or congenital dysplasia of the dens and who also had benign fibrous masses in this region, confirmed at surgery. The association of masses of the craniovertebral junction with chronic atlantoaxial subluxation raises the possibility that the underlying cause of the masses is chronic mechanical irritation. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 0 publications
1
74
0
Order By: Relevance
“…They concluded that the large soft-tissue mass is the sequela of chronic mechanical irritation caused by atlantoaxial subluxation. In contrast, an atypical mass at the posterior of the odontoid process not associated with underlying disease has been reported to be a reactive fibrocartilaginous mass induced by chronic subluxation in the craniovertebral junction [5,6]. The pathomechanism for pseudotumor formation has been postulated to the result of atlantoaxial instability that induces repeated tears and subsequent hypertrophy of the transverse ligaments [8,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the large soft-tissue mass is the sequela of chronic mechanical irritation caused by atlantoaxial subluxation. In contrast, an atypical mass at the posterior of the odontoid process not associated with underlying disease has been reported to be a reactive fibrocartilaginous mass induced by chronic subluxation in the craniovertebral junction [5,6]. The pathomechanism for pseudotumor formation has been postulated to the result of atlantoaxial instability that induces repeated tears and subsequent hypertrophy of the transverse ligaments [8,20].…”
Section: Discussionmentioning
confidence: 99%
“…These non-neoplastic mass lesions are known to be associated with rheumatoid arthritis [1,2], and with hemodialysis [3,4], frequently leading to cervical myelopathy. The masses in the posterior odontoid process, not associated with the underlying disease, have been reported to be reactive fibrocartilaginous masses induced by chronic subluxation of the craniovertebral junction [5,6]. Preexisting atlantoaxial instability has been considered to cause repeated tears and subsequent hypertrophy of the transverse ligament, leading to retro-odontoid pseudotumor [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…8) MR imaging of the retro-odontoid mass in our case showed a striking similarity to pseudotumor, 15) which is a fibrous granulation or fibrocartilaginous mass usually associated with chronic osteoarthrosis 16) or atlanto-axial subluxation. 11) This type of lesion appears as intermediate to low intensity on T 1 -weighted images and mainly low intensity on T 2 -weighted images, consistent with the fibrous composition. 11,15) Other types of retro-odontoid lesions causing myelopathy include rheumatoid pannus, 18) CPPD deposition disease, 1,17) ossification of the transverse ligament, 7,13) herniated disc, 9) and synovial cyst.…”
Section: Discussionmentioning
confidence: 54%
“…11) This type of lesion appears as intermediate to low intensity on T 1 -weighted images and mainly low intensity on T 2 -weighted images, consistent with the fibrous composition. 11,15) Other types of retro-odontoid lesions causing myelopathy include rheumatoid pannus, 18) CPPD deposition disease, 1,17) ossification of the transverse ligament, 7,13) herniated disc, 9) and synovial cyst. 2) Our patient denied any history of trauma, and there was no evidence of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 54%
“…Some authors have called these masses periodontoid pseudotumor [13]. Due to the chronic instability and the mass effect on the spinal cord, they can produce severe myelopathy [15].…”
Section: Introductionmentioning
confidence: 99%